Perspectives of people living with dementia and their care partners about the impact on social health when participating in a co‐designed Dementia café. (18th August 2021) - Innes, Anthea; Chesterton, Lorna; Morris, Lydia; Smith, Sarah K.; Bushell, Sophie
Abstract: Those diagnosed with dementia and those who provide care and support often feel socially isolated with limited opportunities for social engagement, increasing the potential for loneliness and further isolation that is detrimental to social health. This study examined how a co‐designed dementia café impacted on the self‐reported social health of community dwelling people with dementia and their care partners in the North‐West of England. Semi‐structured interviews were conducted at two time periods (summer of 2019 and spring of 2020), with five people living with dementia and eight care partners. The key finding was that participating in the cafés led to a sense of belonging and purpose that was beneficial to well‐being and social health for all participants. Community‐based initiatives that provide opportunities for peer support for the person with the diagnosis and the care partner are essential so that people living with dementia may rebuild their confidence as well as retaining opportunities to socialise.